2012
DOI: 10.1134/s1063774511030291
|View full text |Cite
|
Sign up to set email alerts
|

New criterion for conformational polymorphism

Abstract: An analysis of nonvalent interactions in 29 crystal structures of compounds that have the C a H b N c O d composition (salicylaldoxime, glycine, and 2,4,6,8,10,12 hexaazaisowurzitane) and form polymorphic modifications is performed using molecular Voronoi-Dirichlet polyhedra. It is found that each conforma tional polymorph is characterized by a unique combination of the types of intramolecular and intermolecular nonvalent interactions. It is shown that a criterion which takes into account the total number of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 11 publications
3
47
0
1
Order By: Relevance
“…Using the method of molecular Voronoi–Dirichlet polyhedra, we estimated the average volumes of crotonate, butyrate, and valerate ions over all the compounds in the final database, which were found to be equal to 119(8), 130(12), and 154(9) Å 3 , respectively. Thus, the lengthening of the ligand on one –CH 2 – group from a butyrate to a valerate ion results in expanding the volume of the ligand by about 24 Å 3 , which is in good agreement with the results in ref…”
Section: Resultsmentioning
confidence: 99%
“…Using the method of molecular Voronoi–Dirichlet polyhedra, we estimated the average volumes of crotonate, butyrate, and valerate ions over all the compounds in the final database, which were found to be equal to 119(8), 130(12), and 154(9) Å 3 , respectively. Thus, the lengthening of the ligand on one –CH 2 – group from a butyrate to a valerate ion results in expanding the volume of the ligand by about 24 Å 3 , which is in good agreement with the results in ref…”
Section: Resultsmentioning
confidence: 99%
“…The working capacity of the MMVDP has already been demonstrated by the analysis of non-bonded interactions in crystals of hydrocarbons Serezhkin, Prokaeva, Pushkin, Serezhkina & Kudryashov, 2008;Serezhkin, Prokaeva, Pushkin, Serezhkina & Onuchak, 2008;Serezhkin, Serezhkina, Shevchenko & Pushkin, 2005), metal carbonyls and -complexes , binary oxides and halogenides (Serezhkin et al, 2009a,b) as well as some conformational polymorphs (Serezhkin et al, 2010;Serezhkin et al, 2011;Serezhkin & Serezhkina, 2012). It has been demonstrated that the differences in non-bonded interactions in the structures of conformational polymorphs can be characterized quantitatively based on the total number of nonbonded interactions, their distribution among inter-and intramolecular contacts and the identity of interacting atoms (the k-È criterion).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the differences in non-bonded interactions in the structures of conformational polymorphs can be characterized quantitatively based on the total number of nonbonded interactions, their distribution among inter-and intramolecular contacts and the identity of interacting atoms (the k-È criterion). The goal of the present paper was to verify the k-È criterion (Serezhkin & Serezhkina, 2012) for quantitative estimation of differences between molecular structures in crystals of conformational polymorphs based on the example of substances with the composition C w H x N y O z . The relationship between non-bonded interactions and photochromism of these substances was investigated within the method of molecular Voronoi-Dirichlet polyhedra.…”
Section: Introductionmentioning
confidence: 99%
“…As known [11,12], in this method that takes into account all possible nonbonded contacts rather than only those that are believed to be impor tant or significant, intermolecular interactions are represented by VDP faces of zero rank. It should be noted that the rank of faces (FR) characterizes the minimal number of chemical bonds connecting the atoms whose VDPs share a face [11,12]. It is precisely this characteristic that makes it possible to easily and unambiguously differentiate chemical bonds (for …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the existence in structure II of two types of complexes-[UO 2 (mac)(L) 3 ] + (10) and [UO 2 (mac) 3 ] -(14)-rather than one [UO 2 (mac) 2 (L)] complex (11), like in crystals of III, is presumably caused by different stability of intermolecular hydro gen bonds generated upon the formation of crystals and depending on the composition of amide L mole cules. Disproportionation during crystallization of II results in a more energetically favorable packing of mononuclear complexes of different composition due to relatively strong N-H⋅⋅⋅O hydrogen bonds between them as compared with an alternative packing of iden tical dimers in crystals of III due to relatively weak C-H⋅⋅⋅O hydrogen bonds.…”
Section: Resultsmentioning
confidence: 99%